Tandem mass tag labeled quantitative proteomic analysis of differential protein expression on total alkaloid of Aconitum flavum Hand.-Mazz. against melophagus ovinus - Wang, Xinjian; Yang, Zhen; Zhang, Yujun; Cheng, Feng; Xing, Xiaoyong; Wen, Fengqin; Hu, Yonghao; Chen, Changjiang; Wei, Bin; Bai, Pengxia; Wang, Xuehong; Liu, Yu; et al. (Frontiers in Veterinary Science, 2022)
Melophagus ovinus disease is a common ectoparasitosis, which can lead to the decrease of animal production performance, product quality and even death. Aconitum flavum Hand.-Mazz. has many pharmacological activities including insecticidal, heat-clearing, analgesic and dehumidifying. However, there are few researches focused on the effects and related mechanism of Aconitum flavum Hand.-Mazz. in killing melophagus ovinus. In this study, 11 alkaloids of Aconitum flavum Hand.-Mazz. were detected and its total alkaloid activity was determined. The results showed when the total alkaloid concentration was 64 mg/mL and the treatment time was 16 h, the killing rate of melophagus ovinus reached 100%. Through the observation of the differences in the surface of melophagus ovinus in each experimental group, it was found that the morphology of posterior end of the female melophagus ovinus in the alkaloid treatment group was significantly different from that of the blank and positive control groups, and most of the epidermal tissue was abscissive and missing. Moreover, the enzyme activity determination results of 64 mg/mL group were significantly different comparing with normal control group, while there was no significant difference in other groups. Then, the melophagus ovinus gene library was established by the unreferenced genome transcriptome sequencing, proteomic comparison was performed using tandem mass tag labeled protein detection technology, and finally the samples were quantitatively analyzed by liquid chromatography-mass spectrometry tandem and bioinformatics methods. Based on the above experimental results, it was speculated that Aconitum flavum Hand.-Mazz. total alkaloids may cause the imbalance of protein disulfide isomerases expression by affecting the regulation of Hsp40 cellular protein homeostasis and the oxidation of protein disulfide isomerase and related proteins. This would affect the selective recognition of signal sequence, the targeted transport of Sec 61 and the correct folding of the three-dimensional structure of amino acid chain, weaken the clearance of amino acid chains that cannot be correctly folded, eventually resulting in the killing of melophagus ovinus. This study preliminarily revealed the mechanism of Aconitum flavum Hand.-Mazz. total alkaloids against melophagus ovinus, and provided theoretical basis for the screening of melophagus ovinus action targets and the development of new veterinary drugs.